2018
DOI: 10.21767/2576-3903.100031
|View full text |Cite
|
Sign up to set email alerts
|

Immune Checkpoint Inhibitors in Triple Negative Breast Cancer: What is the Evidence?

Abstract: Breast cancer is the most prevalent breast cancer in women. Despite our deeper understanding of mammary oncogenesis, 20% of breast cancer patients develop metastasis and die. There is a dire need for novel therapies especially for more aggressive subtypes like triple negative (TNBC) and HER2 positive breast cancers. For long, breast cancer was thought to be less immunogenic in nature compared to other solid malignancies like melanoma and non-small cell lung cancer, both later cancers yielding great results wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…5c). These characteristics may indicate a susceptibility to immune checkpoint inhibitors and cyclooxygenase inhibitors in human claudin-low breast cancer [63, 64].…”
Section: Resultsmentioning
confidence: 99%
“…5c). These characteristics may indicate a susceptibility to immune checkpoint inhibitors and cyclooxygenase inhibitors in human claudin-low breast cancer [63, 64].…”
Section: Resultsmentioning
confidence: 99%
“…These features were also characteristic of human claudin-low tumors in the METABRIC cohort [6,7], which showed significantly higher expression levels of both PTGS2 and CD274 compared to non-claudin-low breast tumors (p < 0.001 for both, two-tailed Wilcoxon rank-sum test), and compared specifically to basal-like tumors (p = 0.004 and p < 0.001, respectively) (Fig 5C). These characteristics may indicate a susceptibility to immune checkpoint inhibitors and cyclooxygenase inhibitors in human claudin-low breast cancer [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…Aberrant signaling by VEGFR2 and cMET, as well as modifications of the immune cell population in response to an immune-suppressive phenotype, resulted in a failure of immunotherapy for TNBC [ 9 ]. In TNBC, multiple genomic instabilities and mutations have been associated with immune responses [ 10 ]. A comparative study between TNBC and non-TNBC (NTNBC) showed that TNBC is characterized by higher expression levels of functional gene sets associated with 15 types of immune cells [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%